Evaluate use of over the counter drugs among medical students in a tertiary care teaching hospital - Sood, Megha; Bajaj, Jagminder Kaur; Grewal, Nipunjot (International Journal of Basic & Clinical Pharmacology, 2019)
Background: In our country there is easy availability of drugs over the counter leading to their unintentional misuse and abuse. Over the counter availability of drugs does offer the benefit of easy access to medicines and allows individuals to become in charge of their own health. It is important to understand that medical education can impact the OTC drug use amongst medical students. In order to observe the pattern of OTC drug use among the first and second professional MBBS students we planned this study. The aim of the study was to evaluate use of over the counter (OTC) drugs among medical students in a tertiary care teaching hospital. Methods: Our study was a cross sectional study conducted on first and second professional MBBS students. Authors administered a self structured, prevalidated questionnaire to the students. The data obtained was tabulated, analyzed and the results calculated in percentages. Results: The use of OTC drugs is common amongst undergraduate students. All (100%) the students who participated in the study had used OTC drugs at some point in their life. The common conditions prompting use of OTC drugs include head ache, body aches (74%), fever (72%), respiratory conditions such as: cold (60%), cough (28.5%), abdominal symptoms such as: abdominal pain (14%), gastritis (7.5%), diarrhea (6%), vomiting (5%) and allergies (10%). Very few students reported adverse drug reactions with these drugs. Conclusions: From our study we have concluded that OTC drugs are commonly used amongst medical students. So, periodic training and talks on self medication are necessary for them. Student knowledge in this aspect will help them in future counseling of their patients.